Effectiveness of Happy Spiritual Intervention in Reducing Hallucination Levels Among Schizophrenia Patients - Annisa Mazda Firdaus; Habsyah Saparidah Agustina; Muhammad Zaenal Muttaqin (Journal La Medihealtico, 2025)
Hallucinations are the main symptom of schizophrenia that negatively affect patients’ social and psychological functioning. Reducing the level of hallucinations is crucial, particularly during the recovery phase when patients require a holistic approach to improve their quality of life. Spiritual-based non-pharmacological interventions represent an alternative therapy with the potential to help decrease hallucination levels. The objective of this study was to determine the effect of the happy spiritual intervention on hallucination levels in patients with schizophrenia at the West Java Provincial Mental Hospital. Methods: This study employed a pre-experimental one-group pretest-posttest design with a quantitative approach. The sample consisted of 30 respondents selected through purposive sampling. The happy spiritual intervention was administered for 6 days, with each session lasting 15 minutes. Hallucination levels were measured using the Psychotic Symptom Rating Scale (PSYRATS). Data were analyzed using the Wilcoxon test with a significance level of 0.05. The findings showed a significant effect, namely a reduction in hallucination levels after the intervention (p = 0.001). Conclusion: The happy spiritual intervention significantly reduced hallucination levels in patients with schizophrenia during the recovery phase. This intervention can be used as a complementary Islamic spiritual-based therapy in psychiatric nursing practice and is recommended for routine implementation in mental health facilities